A single-CRD C-type lectin (CgCLec-3) with novel DIN motif exhibits versatile immune functions in Crassostrea gigas. Issue 92 (September 2019) - Song, Xiaorui; Xin, Xiaoyu; Wang, Hao; Li, Hui; Zhang, Huan; Jia, Zhihao; Liu, Conghui; Jiang, Shuai; Wang, Lingling; Song, Linsheng
Abstract: C-type lectins (CTLs), as important pattern recognition receptors (PRRs), are a superfamily of Ca 2+ -dependent carbohydrate-recognition proteins which participate in nonself-recognition and eliminating pathogens. In the present study, a novel CTL (designated as Cg CLec-3) was identified from the Pacific oyster Crassostrea gigas . There was only one carbohydrate-recognition domain (CRD) of 151 amino acid residues within the deduced amino acid sequence of Cg CLec-3. The deduced amino acid sequence of Cg CLec-3 CRD shared low homology with the CRDs of other CTLs in oyster with the identities ranging from 12% to 22%. A novel DIN motif was found in Ca 2+ -binding site 2 of Cg CLec-3. The relative expression level of Cg CLec-3 in hemocytes was up-regulated significantly after the stimulations of bacteria and Pathogen Associated Molecular Patterns (PAMPs). Immunohistochemistry assay showed that Cg CLec-3 protein was mainly distributed in gill and mantle, less in gonad, and could not be detected in adductor muscle and hepatopancreas. The recombinant protein (r Cg CLec-3) could bind lipopolysaccharide (LPS), mannose (MAN) and peptidoglycan (PGN), but not poly (I:C). r Cg CLec-3 exihibited strong binding ability to Vibrio anguillarum and V. splendidus, moderate binding activities to Escherichia coli, Pichia pastoris and Yarrowia lipolytica, weak binding affinity to Staphylococcus aureus and Micrococcus luteus . r Cg CLec-3 could agglutinate microorganisms, in a Ca 2+ -dependent manner and its activity to agglutinate V. splendidus was remarkably higher than that to agglutinate E. coli, S. aureus and P. pastoris . The phagocytic activity of oyster hemocytes was significantly enhanced after incubation with r Cg CLec-3. r Cg CLec-3 also exhibited antibacterial activity against E. coli and S. aureus . The results clearly suggested that Cg CLec-3 in Pacific oyster C. gigas not only served as a PRR involved in the PAMPs recognition and microbes binding, but also functioned as an immune effector participating in the clearance of invaders. Highlights: A single-CRD C-type lectin ( Cg CLec-3) with novel DIN motif was identified from C. gigas. The mRNA transcripts of Cg CLec-3 were up-regulated post the stimulations of PAMPs and bacteria. Cg CLec-3 was mainly distributed in immune organs including mantle and gill. Cg CLec-3 could recognize a variety of PAMPs and agglutinate microorganisms. Cg CLec-3 could enhance phagocytic ability of hemocytes and inhibit the growth of bacteria.